2012
DOI: 10.1073/pnas.1211557109
|View full text |Cite
|
Sign up to set email alerts
|

First-order rate-determining aggregation mechanism of p53 and its implications

Abstract: Aggregation of p53 is initiated by first-order processes that generate an aggregation-prone state with parallel pathways of major or partial unfolding. Here, we elaborate the mechanism and explore its consequences, beginning with the core domain and extending to the full-length p53 mutant Y220C. Production of large light-scattering particles was slower than formation of the Thioflavin T-binding state and simultaneous depletion of monomer. EDTA removes Zn 2þ to generate apo-p53, which aggregated faster than hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 19 publications
4
75
0
Order By: Relevance
“…S2D), indicating a reversible binding of ThT. We discuss further in the accompanying paper why different techniques give different kinetics (23).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…S2D), indicating a reversible binding of ThT. We discuss further in the accompanying paper why different techniques give different kinetics (23).…”
Section: Resultsmentioning
confidence: 85%
“…In the accompanying paper, (23) we explore the consequences of the proposed mechanism for the aggregation of the core domain of Y220C and show the mechanism extends to the fulllength protein.…”
Section: Discussion Complex Kinetics Fits To a Simple Equation Other mentioning
confidence: 99%
“…Increased crowding favors the formation of high-molecular-weight associates at the cost of correct folding, but the presence of chaperones tend to reduce aggregation even in such environment [7]. In vitro studies on protein aggregation indicated variability in the mechanisms of aggregation even for a given protein [8]. Kinetic analysis of in vitro protein aggregation [8][9][10] but also in vivo monitoring of IB formation [11] revealed that aggregate formation can be described as a pseudo-first-order process.…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%
“…In vitro studies on protein aggregation indicated variability in the mechanisms of aggregation even for a given protein [8]. Kinetic analysis of in vitro protein aggregation [8][9][10] but also in vivo monitoring of IB formation [11] revealed that aggregate formation can be described as a pseudo-first-order process. There are two possible mechanisms for IB formation, either IBs start growing from single or limited number of molecules acting as nucleation site or from smaller aggregates which assemble and form larger aggregates [12] .…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%
“…15 in a mechanism that may be a basis for other proteins with multiple aggregation-prone sites. One molecule of p53 unfolds, partially or fully, to expose its aggregation-prone sequences (25,27,28,50). Another molecule is induced to unfold to give the elongation-competent state.…”
Section: Peptides and Peptide Combinations Selectively Kill Cancer Cementioning
confidence: 99%